Estimation of inbreeding coefficient and its effects on birth weight and kid survival in Markhoz goats - Rashidi, A; Almasi, M; Razmkabir, M (Sulaimani Journal for Pure and Applied Sciences, 2014)
Pedigree data of 4186 Markhoz goats which collected from 1993-2012 by Markhoz goat Performance Testing Station in Sanandaj, Kurdistan province of Iran, were analyzed for estimation of inbreeding coefficient and its effects on birth weight (BW) and kid survival (KS). The results showed 58.07% of animals were inbred. The means of inbreeding coefficient for whole and inbred populations were 3.03 and 5.21%, respectively. The trend of inbreeding coefficient was 0.236±0.044 and significant (P<0.05). Maximum of inbreeding coefficient was 31.25%. Effects of inbreeding on BW and KS were estimated by restricted maximum likelihood (REML) method under 12 animal models. The most appropriate model for each trait was determined by Akaike’s Information Criterion (AIC) test. The regression coefficients of BW and KS on inbreeding coefficient were -0.50±1.57 gm and - 0.17±0.10 percent, respectively. The results obtained in the present study showed inbreeding had not significant effects on BW and KS (P>0.05).
Keywords: inbreeding coefficient birth weight kid survival